IS TIGECYCLINE EFFECTIVE IN CONTINUOUS AMBULATORY PERITONEAL DIALYSIS RELATED PERITONITIS - Tartar, Ayse Sagmak; Ozden, Mehmet; Dogukan, Ayhan; Akbulut, Ayhan; Demirdag, Kutbeddin; Tartar, Tugay (Carbone Editore, 2017)
Introduction: To compare conventional intraperitoneal vancomycin-amikacin and intravenous tigecycline treatments for continuous ambulatory peritoneal dialysis (CAPD) related peritonitis. Materials and methods: Patients diagnosed with CAPD-related peritonitis were randomized into two groups as intravenous tigecycline group (n = 10) and intraperitoneal vancomycin-amikacin group (n = 20). Patients accompanied by peritonitis exit site infection, peritonitis based on Pseudomonas or fungi were excluded from the study. Results: As for 24th and 48th hours peritoneal fluid leukocyte count of patients, significant difference was not observed in tigecycline group at 24th hours, while significant reduction was observed in vancomycin-amikacin group (p < 0.05). A significant reduction was observed at 48th hours in both groups. As for the treatment response, abdominal pain decreased in 18 (90%) patients in vancomycin-amikacin group, decreased in 8 (80%) patients in tigecycline group at 48th hours. It was detected that dialysate leukocyte count decreased significantly (p > 0.05). Relapse was observed in 4 (40%) patients in tigecycline group, while not observed in vancomycin-amikacin group (p < 0.05). Conclusion: Tigecycline proved its effectiveness in the clinical use for complicated intra-abdominal infections. However, it was considered that tigecycline cannot be alternative to vancomycin-amikacin treatment for continuous ambulatory peritoneal dialysis related peritonitis.
Keywords: Tigecycline; vancomycin; continuous ambulatory peritoneal dialysis; peritonitis